Alien crosstalk - Stuart-Watson, Andrew Joseph (Rhodes University, Faculty of Humanities, School of Languages and Literatures)
Alien Crosstalk
Keywords: Creative writing (Higher education) -- South Africa; Diaries -- Authorship; Short stories, South African (English) 21st century; South African essays (English) 21st century; American fiction History and criticism